Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Rantepao - Atmisridita Bumbungan; Rati Pundissing; Mince Batara (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the factors that influence taxpayer compliance in paying land and building taxes in Rantepao sub-district. To achieve this goal, qualitative descriptive research methods were used. The analysis techniques used are data reduction, data presentation, conclusions and verification. Based on the results of data analysis, a discussion of the factors that influence taxpayer compliance in paying land and building taxes in Rantepao sub-district has been carried out using five predetermined indicators, namely the condition of the tax administration system, service to taxpayers, tax law enforcement, tax rates, knowledge. taxation. The results of the research findings show that the condition of the tax system being implemented is running well and effectively, services to taxpayers have been carried out well, law enforcement has been carried out, tax rates are appropriate, knowledge is still very low.